Description of current status of implementation and management of cardiac arrest in China - Shuai Liu; Huadong Zhu; Nan Zhang (Scientific Reports)
Abstract Variation in the incidence, survival rate and factors associated with survival after cardiac arrest in China is reported. Some studies have tried to fill the knowledge gap regarding the epidemiology of cardiac arrest in China but were unable to identify reasons for the reported differences. Therefore, the purpose of this study was to describe Chinese management of cardiac arrest, particularly from the perspective of compression, ventilation, monitoring, treatment, and extracorporeal cardiopulmonary resuscitation. An online questionnaire with 56 questions was designed about demographic characteristics, management of cardiac arrest, compression, ventilation, treatment and medicine, as well as advanced life support and resuscitation skill training. A total of 814 copies of questionnaire were received from 23 provinces, 4 autonomous regions and 4 municipalities of China. Results were combined with official information on population density. Throughout China, hospitals resuscitate according to the guideline, however, there are still differences varies in implement with regard to chest compression, ventilation, medicine, monitoring, as well as advanced life support and resuscitation skills training because of economical and developmental level from different regions. All the startup of chest compression is manual, whereas mechanical compression instruments are increasingly involved in sequential resuscitation. Most of clinicians rotate during resuscitation every five cycles other than the guideline recommends every 2 min or when they are tired. About half of the participants don’t build the advanced airway rather than use bag valve mask to ventilate, and 75% of the rest use mechanical ventilation whether they succeed to ROSC. Most of rescuers choose endotracheal intubation which is consistent with many other clinical trials results. Various compression feedback devices play increasingly significant roles in assessment of ROSC. More and more regional hospitals have access to ECPR and implement TTM, but still lead to various divergences. Thus, more elaborate clinical trials need to be designed to verify and explore every procedure in the CPR life cycle.